What happens after midnight eaudiobook - Walther, K. L. (Tantor Media, 2023)
Lily Hopper has two more weeks until she's officially finished with boarding school. With graduation quickly approaching Lily is worried that she's somehow missed out on the fun of being in high school. So, when she receives a mysterious note inviting her to join the anonymous senior class Jester in executing the end-of-year prank, Lily sees her chance to put her goody-two-shoes reputation behind her. When Lily realizes the Jester is none other than Taggart Swell, her ex-boyfriend, she's already in too deep to back out. Lily might've dumped Tag, but she still has major feelings. Plus, his brilliant plan to steal the school's yearbooks, targets none other than Lilly's prom date: the Senior Class President, Daniel. As the group of pranksters hide cryptic clues across campus for Daniel to find, Lily and Tag find themselves in close quarters. As the exes dodge Campus Safety guards, night owl teachers, a troop of freshmen, and even Daniel himself, new sparks fly. But old hurts and painful secrets refuse to be ignored. And with graduation on the horizon, Lily can only hope that breaking the rules will help mend her heart.